2-x=11(x-1)

Simple and best practice solution for 2-x=11(x-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2-x=11(x-1) equation:


2-x=11(x-1)

We simplify the equation to the form, which is simple to understand
2-x=11(x-1)

Reorder the terms in parentheses
2-x=+(+11x-11)

Remove unnecessary parentheses
+2-x=+11x-11

We move all terms containing x to the left and all other terms to the right.
-1x-11x=-11-2

We simplify left and right side of the equation.
-12x=-13

We divide both sides of the equation by -12 to get x.
x=1.08333333333

See similar equations:

| (697)(10)= | | 17x^2-11x=0 | | 2x^4y^4+x^3y^3-15x^2y^2=0 | | 36x-9=63 | | 6(4y+14)-13(9y)=100 | | x^2+18x+59=0 | | 8.1x+61.68=-11.9x+60.44 | | 6a^4+7a^2-20=0 | | x*x*x*x-30x*x+125=0 | | 7.2x-3.9=3.3 | | a^4+2a^2-24=0 | | 4x*x*x*x=12x*x | | 5(6z-1)-2(z+3)=21(z+1) | | y^4+y^2-42=0 | | -13x+8x= | | -3(t-4)-(t+9)=3 | | 1.5-2.5x+8.5=-2.5 | | 15n-3/2=6 | | 44=122 | | 7-2-(-8)-11= | | -8(t-3)-(t+1)=8 | | -14+58-(-13)-16= | | 5w^2=5w-10 | | 5+8(x-1)=5-2(x-9) | | 36+(-52)+31= | | -15+12+(-27)+25= | | y=9(0)+3 | | 5+5(x-6)=6-6(x-3) | | y=9(3)+3 | | 2+4=-6 | | y=93+3 | | h=-4t^2+20t+7 |

Equations solver categories